Pragmatic Interpretations of Idiomatic Phrases in Mitski’s Lyricism - Ramadhan, Kevin Bintang; Riansyah, Jevera Edni (ITScience (Information Technology and Science), 2025)
This study examines the use of idiomatic phrases in Mitski’s selected song lyrics to explore their types, meanings, and pragmatic interpretations. Using a descriptive qualitative approach, ten songs were analyzed: I Bet on Losing Dogs, I Don’t Like My Mind, Bag of Bones, Working for the Knife, I’m Your Man, Fireworks, Stay Soft, My Love Mine All Mine, Washing Machine Heart, and Lonesome Love. Based on Fernando’s framework, three types of idioms were identified: pure idioms, semi-idioms, and literal idioms. The findings indicate that literal idioms are the most dominant, appearing six times, followed by five semi-idioms and four pure idioms. These idioms serve not only as linguistic features but also as representations of Mitski’s emotional depth and psychological expression. Pragmatically, idioms in Mitski’s lyrics convey themes of vulnerability, self-reflection, and inner conflict that extend beyond their literal meaning. This study concludes that these idiomatic expressions function as both artistic and pragmatic tools, enabling the communication of layered emotions and highlighting the complex interplay between language, context, and human experience.